Penerapan Teknik Ice Breaking dalam Membangkitkan Motivasi Belajar Siswa Kelas V SD Negeri 72 Pagar Alam Sumatera Selatan - Yulia, Rizka; Yahan, Rahman; Subhi, Imam (CV. Creative Tugu Pena, 2024)
Learning motivation is an important factor in supporting student learning success, but learning motivation is influenced by the ongoing learning atmosphere, a boring, stiff and passive learning atmosphere will influence student learning motivation. Ice Breaking is an activity that aims to break down the stiff and boring learning atmosphere. The type of research used is descriptive qualitative research, with data collection techniques through interviews, observation and documentation, while the analysis used is a pattern of reduction, data display and drawing conclusions. From this study, the results showed that Ice Breaking was able to raise students' learning motivation. This can be seen from the indication of an increase in the average student learning rate from 67.8 to 80.4. Keywords: Ice Breaking, Learning Motivation Learning motivation is an important factor in supporting student learning success, but learning motivation is influenced by the ongoing learning atmosphere, a boring, stiff and passive learning atmosphere will influence student learning motivation. Ice Breaking is an activity that aims to break down the stiff and boring learning atmosphere. The type of research used is descriptive qualitative research, with data collection techniques through interviews, observation and documentation, while the analysis used is a pattern of reduction, data display and drawing conclusions. From this study, the results showed that Ice Breaking was able to raise students' learning motivation. This can be seen from the indication of an increase in the average student learning rate from 67.8 to 80.4. Keywords: Ice Breaking, Learning Motivation